Endometriosis Treatment: Nanoparticle‐Based Platform for Activatable Fluorescence Imaging and Photothermal Ablation of Endometriosis (Small 18/2020). Issue 18 (7th May 2020) - Moses, Abraham S.; Taratula, Olena R.; Lee, Hyelim; Luo, Fangzhou; Grenz, Tanner; Korzun, Tetiana; Lorenz, Anna St; Sabei, Fahad Y.; Bracha, Shay; Alani, Adam W. G.; Slayden, Ov D.; Taratula, Oleh
Abstract : In article number 1906936, Ov D. Slayden, Oleh Taratula, and co‐workers present a nanomedicine approach for endometriosis treatment. Photo‐responsive nanoparticles concurrently delineate and ablate endometriosis tissue xenografts in mice employing real‐time fluorescence imaging and photothermal therapy. Following intravenous injection, nanoparticles activate their fluorescence in endometriotic lesions. Excitation by near‐infrared light produces heat within endometriotic tissues, resulting in their complete eradication. This approach could aid surgeons in identifying and eliminating endometriosis.